The evening and the morning [compact disc, unabridged] - Follett, Ken (The Kingsbridge series, 2020)
It is 997 CE, the end of the Dark Ages. England is facing attacks from the Welsh in the west and the Vikings in the east. Those in power bend justice according to their will, regardless of ordinary people and often in conflict with the king. Without a clear rule of law, chaos reigns. In these turbulent times, three characters find their lives intertwined.